If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2Y+6=3Y-9
We move all terms to the left:
-2Y+6-(3Y-9)=0
We get rid of parentheses
-2Y-3Y+9+6=0
We add all the numbers together, and all the variables
-5Y+15=0
We move all terms containing Y to the left, all other terms to the right
-5Y=-15
Y=-15/-5
Y=+3
| 17=2x+3x+7 | | -20n=-140 | | 3x+9+x=90 | | 3k=54 | | -3x+2=−3x+2=2x+372x+37 | | 12x+2+110=180 | | n/16-9=3 | | 16x-4=120 | | 16x-4=129 | | 252=d+3 | | 1a+2345433=1 | | (2x+30)+(x+50)=180 | | 12x-5=125 | | 5x-5+x=47 | | p-36/9=4 | | 18+17y=1 | | 96=-6m | | 11/7=10/v | | (x+4)(x+4)-(x-6)(x-6)=10x | | t+1.9=2.1 | | 11/7 = 10/v | | 11x-2=5-3x | | -9=-7+d | | 2(9x+20)=10x+8 | | 3p-5=9p-23 | | 117 = 10v | | 7x-14=28 | | 3z+(−10)=−19 | | y(4)+3y′′−4y=0 | | 50-x+2x=90 | | 27=18+y | | 7/10x+16=2 |